Pengaruh harga dan kualitas produk terhadap keputusan pembelian di Kopi X - Rianti, Alfina Syahla (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2023)
Business development is quite rapid and growing, one of which is a coffee beverage company. currently coffee beverage companies are very diverse, therefore there is a lot of competition between one coffee company and another. One of them is the Kopi Memories beverage product which is produced with quality beans. Therefore this study aims to determine the effect of price and product quality on purchasing decisions for the Kopi Memories brand. This research method uses a type of quantitative research with a purposive sampling technique. The population in this study are consumers who consume or buy the Kopi Memories brand with a total sample taken of 50 respondents. The data analysis method in this study is to use Validity, Reliability, Classical Assumption tests, Multiple linear regression analysis, and Hypothesis testing. The results of this study show that V Price and product quality variables have a positive and significant effect both partially and simultaneously on purchasing decisions at Kopi X.